Comparison of Adaptive and Nonadaptive Gap Detection in Noise Test in Typically Developing Children and Adults - Veeranna, Sangamanatha Ankmnal; Christensen, Lyerly; Candace-Ann Chapman, Jennifer (Journal of the American Academy of Audiology, 2024)
Purpose The purpose of this study is to examine whether the gap detection thresholds (GDT) obtained are similar between an adaptive and nonadaptive procedure in children and adults.Study Design Standard group comparison.Study Sample Eighteen typically developing children and 20 young adults with hearing thresholds of 25 dB HL or lower participated in this study.Methods Forced choice (FC) adaptive GDTs were obtained using psychoacoustic software, and nonadaptive GDTs were obtained using a clinically available gap in noise (GIN) test.Results Both children and adults showed significantly lower GDTs for the FC adaptive procedure when compared with thresholds obtained using the nonadaptive GIN test. GDTs were less variable for FC adaptive procedure when compared with the nonadaptive procedure.Conclusion Lower and less variable GDTs can be obtained from children and adults using an FC adaptive procedure.
Keywords: gap in noise; adaptive procedure; gap detection threshold